Biochemical Pathways in Neonatal Intestinal Atresia: Vascular and Genetic Perspectives - Pranandi, Ian (Journal of Neonatal Surgery, 2025)
Neonatal intestinal atresia (NIA) is a congenital condition characterized by the obstruction or absence of a segment of the intestine, leading to life-threatening complications in neonates. The etiology of NIA is multifactorial, involving both vascular and genetic factors. Vascular disruptions during fetal development may lead to ischemic necrosis and resorption of intestinal segments, while genetic mutations affecting developmental pathways contribute to structural anomalies. The involvement of key signaling pathways, including Notch, Wnt, and Hedgehog, suggests that molecular disruptions play a crucial role in intestinal morphogenesis. Additionally, epigenetic modifications and extracellular matrix defects have been implicated in the pathophysiology of NIA, further highlighting the complexity of its developmental origins. Despite advances in prenatal imaging and neonatal surgery, NIA remains a significant cause of morbidity, often requiring extensive surgical intervention and long-term nutritional support. Early genetic screening and fetal Doppler studies may provide better risk stratification and earlier diagnosis, improving perinatal outcomes. Furthermore, emerging research on targeted molecular therapies and gene-editing technologies, such as CRISPR-Cas9, offers promising avenues for future intervention. Current studies suggest that gene-environment interactions, particularly maternal health factors and in utero exposures, may influence the severity and manifestation of NIA. Given the multifaceted nature of this disorder, a comprehensive understanding of its biochemical pathways is crucial for developing effective treatment strategies. This literature review explores the vascular and genetic mechanisms implicated in NIA, with an emphasis on their molecular underpinnings and clinical implications. Advances in stem cell research and tissue engineering may provide alternative therapeutic options in the future, potentially reducing dependence on surgical interventions. By elucidating the intricate interactions between genetic and environmental factors, novel approaches in diagnosis, prevention, and treatment can be developed to improve patient outcomes and quality of life.